Maternal Deprivation Increases Anxiety- and Depressive-Like Behaviors in an Age-Dependent Fashion and Reduces Neuropeptide Y Expression in the Amygdala and Hippocampus of Male and Female Young Adult Rats - Miragaia, Alexandra S.; de Oliveira Wertheimer, Guilherme S.; Consoli, Amanda C.; Cabbia, Rafael; Longo, Beatriz M.; Girardi, Carlos E. N.; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2018)
Maternal deprivation for 24 h produces an immediate increase in basal and stress-induced corticosterone (CORT) secretion. Given the impact of elevated CORT levels on brain development, the goal of the present study was to characterize the effects of maternal deprivation at postnatal days 3 (DEP3) or 11 (DEP11) on emotional behaviour and Neuropeptide Y immunoreactivity (NPY-ir) in the basolateral amygdala and dorsal hippocampus of male and female rats. Litters were distributed in control non-deprived (CTL), DEP3 or DEP11 groups. In Experiment 1, within each litter, one male and one female were submitted to one of the following tests: novelty suppressed feeding (NSF), sucrose negative contrast (SNCT) and forced swimming (FST), between postnatal days 52 and 60. In Experiment 2, two males and two females per litter were exposed to the elevated plus maze and one hour later, perfused for investigation of NPY-ir, on PND 52. The results showed that DEP3 rats displayed greater anxiety-like behaviour in the NSF and EPM, compared to CTL and DEP11 counterparts. In the SNCT, DEP3 and DEP11 males showed less suppression of the lower sucrose concentration intake, whereas all females suppressed less than males. Both manipulated groups displayed more immobility in the FST, although this effect was greater in DEP3 than in DEP11 rats. NPY-ir was reduced in DEP3 and DEP11 males and females in the basolateral amygdala, whereas in the dorsal hippocampus, DEP3 males showed less NPY-ir than DEP11, which, in turn, presented less NPY-ir than CTL rats. Females showed less NPY-ir than males in both structures. Because the deprivation effects were more intense in DEP3 than in DEP11, in Experiment 3, the frequency of nursing posture, licking-grooming and interaction with pups was assessed upon litter reunion with mothers. Mothers of DEP11 litters engaged more in anogenital licking than mothers of DEP3 litters. The present results indicate that maternal deprivation changed affective behaviour with greater impact in the earlier age, and reduced the expression of NPY in emotion-related brain areas. The age-dependent differential effects of deprivation on maternal behaviour could, at least in part, explain the outcomes in young adult rats.